Isolation, Antimicrobial activities, Antioxidant Scavenging activities and Trace Element Investigation of Isolated Actinomycetes spp. in Kalar, Iraqi Kurdistan Region - Saman Mohammad Mohammad Amin (Zanco Journal of Pure and Applied Sciences, 2021)
The poor prognosis of the most microbial pathogenic diseases, due to acquiring resistance against the most convenient antimicrobial medication, encourages researchers to find out a new approach to obtain a novel medication. The current study was aimed to obtain new actinomycetes strains or their novel bioactive metabolites. Eleven isolates were found from 45 distinct non-farming soils in Kalar, Iraqi Kurdistan Region. The non-farming soil 2 (NFS2) isolate was demonstrated as the most effective isolate among all other isolates when tested for primary antimicrobial screening. In addition, in case of crude extract, the NFS2 confers great antimicrobial activities particularly against Gram-positive bacteria Staphylococcus aureus ATCC 25923 and Micrococcus luteus ATTC 9341, as well as, against Candida albicans ATCC 10231, with inhibition zones diameters, 25.5, 33.5 and 30.5 mm respectively. However, the isolate has no any antibacterial responses against Gram-negative bacteria, using all types of extracts including crude extract and organic solvent extracts. The crude extract exhibited the powerful antioxidant and H2O2 scavenging activities recording 93.46% with 30mg/ml and 43.94% with 1.25 mg/ml respectively. Investigating the trace elements concentration in broth cultures yeast malt extract broth (ISP2) by inductively coupled plasma (ICP), for confirming the value of these elements particularly (Ca, Fe, K, Na, P, Sr, Mg, and Zn). Primarily, these elements were either exhausted or produced during the fermentation process. Furthermore, manipulating the trace elements concentration will play a crucial role in enhancing or diminishing the final secondary metabolites products in actinomycets isolates.